The Effect of Using Competitive Style (Self, Comparative and Team) On Learning Scoring In soccer for Second grade Secondary School Students - Abdul Hussein, Mohammed; Qasem, Mohammed (Journal of Physical Education, 2016)
The importance of the research lies in identifying the best teaching methods for learning scoring in second grade secondary school students. The problem of the research was in not giving enough repetitions for students during performance. The aim of this research was identifying the effects of using competitive style on students’ learning scoring in soccer. The researchers used the experimental method. The subjects were second grade students. The concluded that there is a positive effect in using competitive style and recommended using competitive styles on students results showed development in the posttests compared to the pretest. The researchers